Preparedness to Thai SMEs on Cognitive Ability Worthily in Big Data towards 5G on Sustainable Business Performance in the New Normal - Phungphol, Wilai (Human Resource and Organization Development Journal, 2021)
The research aimed to study 1) the cognitive ability of characteristics in Big data for Thai SMEs management worthily, 2) the preparation on sustainable business performance for Thai SMEs in the new normal, and 3) creating a Big data standard user manual on 5G network. The study used qualitative and quasi-experimental researches conducted 40 informants’ purposive sampling in Chiangmai, Udonthani, Bangkok, Chonburi, and Suratthani. The outcomes revealed Technology-Driven - Enthusiastic cover Rapturous - Good Governed - Courageous - Initiative. The cognitive abilities have supported Thai SMEs to 1) manage enormous data, 2) process fast data on 5G network, 3) handle a variety of business data cost-effectively, 4) investigate the accuracy of the Big data on 5G. 5) carefully analyze the variances of Big data, 6) utilize the cost-effective data for customers and employees parallel to hygiene affecting sustainable performance in the new normal. Finally, this study also found a reliable Big data manual for preparing Thai SMEs as well.